Efecto de cinco dosis de humus de lombriz en el cultivo de cebolla roja (Allium cepa l.), en suelos ácidos, sector Aucaloma – Lamas – Perú - Fababa Mori, Ling Fulgencio (2012)
This study was conducted with the objectives to study comparatively the behavior of the onion, red variety Arequipeña with localized application of different doses of vermicompostin acid soils, seeking to improve the performance and profitability of the crop in the farm Aucaloma University San Martín national-Tarapoto, located in SectorAucaloma15 km from Tarapoto, following the road to San Antonio of understanding Cumbaza San Roque district Lamas province and San Martín region. The experimental design was randomized complete block RCBD with 6 treatments and 4 replications of evaluations yielded the following results: The vermicompost of 3.0, 2.5, 2.0 and 1.0 t/ha, took effect in cultivation with respect to the height (44.95, 44.73, 43.33 and 42.58 cm), whereas treatment with 3.0, 2.5, 2.0, 1.5, and 1.0 t/ha of humus obtained larger number of leaves / plant (5.9, 5.88,5.76,5.73and 5.7), while in the treatment with 3.0, 2.5, 2.0 and 1.0 t/ha of humus were obtaineda larger diameter bulb (4.80, 4.48, 4.2, 4.15 cm). With doses of 1.5 and 2.5 t/ha of humus was obtained from bulbs longer (6.89 and 6.86). Doses of 3.0 and 2.5 t/ha (89.63 g, 87.00 g fresh weight and 86.33 g, 84.45 g dry weight) of bulb sat harvest and also obtained the highest yield (21023.1 kg/ ha, 20407.4 kg/ha in fresh and 20249.1 kg/ha, 19809.3 kg/ha dry), with profitability of 1.68 cents back for each new sun sun reversed.